Pengaruh Digital Marketing Dan Kualitas Pelayanan Terhadap Keputusan Penggunaan Layanan Transportasi Online Maxim Di Kota Bogor - Soedargo, Bayu Prasetyo; Pratama, Rafi Zahran; Fahsani, Donny Hendry (Jurnal Aplikasi Bisnis Kesatuan, 2024)
This study aims to find out: 1) how much digital marketing influences the usage decisions for Maxim's online transportation services in Bogor, 2) how much service quality influences the usage decisions for Maxim's online transportation services in Bogor, and 3) how much digital marketing and service quality together influence the usage decisions for Maxim's online transportation services in Bogor. This research is quantitative. The research sample was 150 Maxim’s user respondents. The sampling method used is non-probability sampling with a purposive sampling technique, where every element in the population has an equal chance of being selected. Data collection was done using a questionnaire. The research instruments were tested for validity and reliability. Data analysis and testing techniques included multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results show that digital marketing and service quality have positive and significant influence on the usage decisions for Maxim's online transportation services in Bogor City, both individually and together. The coefficient of determination, with an R Square value of 0.392 (39.2%), indicates that digital marketing and service quality together explain 39.2% of the usage decisions, while the remaining percentage is influenced by other factors not examined in this study. Keywords : Digital Marketing, Service Quality, dan Usage Decision